2010
DOI: 10.1017/s1751731110000972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying proportions of concentrates on ruminal-reducing power and bacterial community structure in dry dairy cows fed hay-based diets

Abstract: The objectives of this study were to evaluate the influence of diet composition on ruminal parameters, more particularly redox potential (E h ). Four Holstein dry dairy cows, fitted with ruminal cannulas, were allocated in a 4 3 4 Latin square design. They were given four experimental hay-based diets D0, D25, D42 and D56 consisting of 0%, 25%, 42% and 56% of ground wheat and barley concentrate mixture, respectively. They were fed at a daily feeding rate of 8.0 kg DM per cow during a 24-day experimental period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…These physico-chemical observations were to be compared with the microbiological data obtained for both diets: the molecular fingerprint of bacterial communities differed significantly by 29% between cows receiving LL and AL. Thus, present results put forward that the ruminal reducing status varies with the diet of animals as already observed by Monteils et al [42] and suggested by Julien et al [16] in dairy cows fed a fiber-or a starch-based diet.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These physico-chemical observations were to be compared with the microbiological data obtained for both diets: the molecular fingerprint of bacterial communities differed significantly by 29% between cows receiving LL and AL. Thus, present results put forward that the ruminal reducing status varies with the diet of animals as already observed by Monteils et al [42] and suggested by Julien et al [16] in dairy cows fed a fiber-or a starch-based diet.…”
Section: Discussionsupporting
confidence: 84%
“…Measurements of pH and redox potential (E h ) were realized over 3 consecutive days (d 15 to d 17 and d 27 to d 29) using the ex vivo method described by Julien et al [16]. For each cow, ruminal pH and E h were recorded hourly over a 9-h period from 1 h before to 8 h after the morning meal (T −1 to T +8 ).…”
Section: Ruminal Physicochemical Measurements and Fermentative Paramementioning
confidence: 99%
“…Ingredient composition of the concentrate mixture in the present study contained 97% barley. Barley is more fermentable in the rumen in comparison to other diets like corn (Granzin 2004;Lanzas et al 2007;Mohammed et al 2010) and therefore increased ruminal TVFA concentration (Khorasani et al 2001;Au et al 2010;Julien et al 2010) was observed. Higher concentration of TVFA production in group 2 is due to concentrate feeding, and this led to a decrease in ruminal pH both at 0 and 4 h of feeding concentrate.…”
Section: Discussionmentioning
confidence: 97%
“…The pH and E h measurements were realized in vivo on the donor cows each hour from the morning meal (T0) to 8 h after (T8) by means of the method described by Julien et al [8], during the day immediately following each day of in vitro cultures. Ruminal fluid was sampled with 10% of HgCl 2 (2% wt/vol) at T0 and T8 for subsequent volatile fatty acids (VFA) determination.…”
Section: In Vitro Experimental Proceduresmentioning
confidence: 99%
“…In the rumen, some authors were interested in measuring E h to get a better insight in its factors of variation. So, ruminal E h tended to be 45 to 100 mV lower in ruminants fed a hay diet (70% to 100% of forage) than in those fed a concentrated diet (40% to 80% of concentrate) [6]- [8]. In cows, Julien et al [9] observed a relation between level of dry matter intake (DMI) and ruminal E h which could vary from −210 to −165 mV, for a low (8 kg of DMI) and high (21 kg) level of DMI respectively.…”
Section: Introductionmentioning
confidence: 99%